Emerging insect pests problems in basil (Ocimum basilicum) and their management - Kedar, Santosh C; Navik, Omprakash; Kumaranag, K M (Indian Horticulture, 2026)
Basil (Ocimum basilicum L.) also known as ‘Tulsi’, is an important medicinal and aromatic plant, widely cultivated in India for its essential oil, used in pharmaceuticals, cosmetics, food, and traditional medicine. However, increased cultivation has led to rising insect pest problems, causing significant yield and quality losses. Basil is attacked by leaf-eating insect pests, such as leaf folder, perilla leaf moth, Helicoverpa armigera, tobacco caterpillar, and Bihar hairy caterpillar, as well as sap-sucking pests like lace bugs, aphids and thrips. These pests damage foliage, shoots, buds, and flowers, resulting in reduced photosynthesis, stunted growth, and lower essential oil yield. Climate variability and intensive monocropping have further aggravated pest incidences. Timely diagnosis of pest problems, regular monitoring, and preventive measures are essential for effective management. Integrated Pest Management (IPM) strategies involving neem based formulations, biological control, mechanical removal, pheromone and light traps, and conservation of natural enemies ensure sustainable and residue free basil production. This article provides practical guidelines for farmers and extension personnel to manage key insect pests and safeguard basil cultivation.